A preliminary report of maximum voluntary bite force of young Indian population - Madhu Ranjan; Bishnupati Singh; Surender Kumar; Tushar; Priya Rani; Anupama Singh (Wolters Kluwer Medknow Publications, 2024)
Introduction: The measurement of bite force is increasingly gaining importance in dentistry. This preliminary report evaluates the maximum voluntary bite force (MVBF) of young healthy individuals with normal occlusion and correlates the effect of age and gender with the maximum bite force (MBF). Materials and Methods: 405 participants in the age group of 18 to 40 years were selected from the outpatient department meeting inclusion and exclusion criteria. MVBF was measured with the help of a digital device called "Byte" at incisors, right first molar, and left first molar region. Results: There was a strong correlation between age with bite force. Bite force increased with age. Males had more bite force than females. The posterior region had higher bite force than the anterior region. Conclusion: Measurement of bite force is very important for every patient undergoing restorative treatment. The "Byte" device was found to be very efficient.